Utilizing social media marketing (SMM) initiatives to create customer brand engagement (CBE) and brand loyalty: Mediating impacts of brand trust, brand awareness, and brand image - Salsabila Salsabila; Sri Rahayu Hijrah Hati (Jurnal Manajemen dan Pemasaran Jasa, 2024)
This study investigates the influence of brand interactivity, brand involvement, and SMM elements (entertainment, trendiness, customization, EWOM, and interaction) on brand-related outcomes (brand trust, brand awareness, brand image, and brand loyalty) through the role of social media CBE. An online survey was used to collect information from a total of 298 participants who are followers of Netflix Indonesia’s Instagram page selected through purposive sampling. SEM-PLS was used to analyze the collected data. This study finds the significant influence of some of the analyzed SMM variables on CBE and brand-related outcomes. This study also shows the mediating role of brand trust, brand image, and brand awareness. However, the findings do not show any significant influence from entertainment, customization, interaction, and brand interactivity toward CBE. Therefore, the result of this study can be used as a refernce for futher studies and marketers when strategizing social media campaigns.